SURFACE SALINITIES IN THE STRAIT OF MALACCA - Soeriaatmadja, Raden E. (Marine Research in Indonesia, 1956)
A continuous northwest-going current prevails in the Strait of Malacca throughout the year, except June and August, when the currents are very weak and sometimes reversedÂ  in the .southern part. The southern part of the Strait of Malacca is influenced by the currents. These currents transport low saline water into the Strait during the southwest monsoon and high saline water from the South China Sea during the northeast monsoon. In the northern part, the rainfall is of greater importance for the variations of the surface salinity and a strong correlation between rainfall and surface salinities is found in this region. It is unlikely that Indian Ocean water penetrates the South China Sea.